Lack of Hypothalamus Polysialylation Inducibility Correlates With Maladaptive Eating Behaviors and Predisposition to Obesity - Brenachot, Xavier; Nédélec, Emmanuelle; Ben Fradj, Selma; Boudry, Gaelle; Douard, Véronique; Laderrière, Amélie; Lemoine, Aleth; Liénard, Fabienne; Nuzzaci, Danaé; Pénicaud, Luc; Rigault, Caroline; Benani, Alexandre (Frontiers in Nutrition, 2018)
High variability exists in individual susceptibility to develop overweight in an obesogenic environment and the biological underpinnings of this heterogeneity are poorly understood. In this brief report, we show in mice that the vulnerability to diet-induced obesity is associated with low level of polysialic acid-neural cell adhesion molecule (PSA-NCAM), a factor of neural plasticity, in the hypothalamus. As we previously shown that reduction of hypothalamic PSA-NCAM is sufficent to alter energy homeostasis and promote fat storage under hypercaloric pressure, inter-individual variability in hypothalamic PSA-NCAM might account for the vulnerability to diet-induced obesity. These data support the concept that reduced plasticity in brain circuits that control appetite, metabolism and body weight confers risk for eating disorders and obesity.